DIRECTIONS OF IMPROVING THE PERFORMANCE OF THE PROJECT TEAM MANAGEMENT IN OTG - YAROSHENKO, Ihor; AVEDYAN, Lyudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article considers the stages of creating a project team in the OTG (formation, period of activation of participants, period of normal functioning, reorganization, disbandment). In this article, the emphasis is on the first stage of this process, which consists of three substages (diagnostic, training, support). The work also describes the goals of creating project teams (changing the set of goals or priorities; analysis and distribution of the way of work; analysis of norms, the way of decision-making, communications; determining the relationships between people who perform the work), as well as four main approaches to the formation of teams (goal-setting, interpersonal, role-based, problem-oriented). The article is devoted to the substantiation of directions for improving the effectiveness of project team management in united territorial communities. It was determined that the management of the project team is one of the important issues in the framework of ensuring the effective project activity of the organization, because there is an increase in the complexity of projects and, accordingly, the importance of risk management, in addition, it is necessary to take into account emergency crisis situations, a large number of stakeholders, and the development of technologies, which is actively taking place . The reasons for improving the project team management process are analyzed. Priority steps to increase the effectiveness of project team management are proposed. The need for the formation of a competence matrix was determined, which involves the implementation of such steps as: defining roles and tasks; definition of competences; assessment of team competencies; matrix filling. The need to use appropriate software to increase the effectiveness of project communication in the process of project activities of the OTG is substantiated. It was determined that communications in the OTG occupy an important place in terms of improving the project team management process. Accordingly, the need to develop an effective communication policy is substantiated, which will contribute not only to increasing the efficiency of project activities, but also to optimizing the level of management of the project team. It has been proven that improving the project team management process allows you to maintain control over the project budget and avoid unexpected costs. This allows to ensure efficient use of resources and to determine the possibility of achieving appropriate results. But in the end, it allows for better communication between project participants, which contributes to better cooperation and achieving better results.